PROBLEMATIKA PEMBELAJARAN MATEMATIKA PADA MATERI STATISTIKA SMP KELAS IX - Heri Satriawan (Jurnal Pembelajaran Matematika, 2018)
Abstract: The present study is addressed to inform the problems experienced by students in statistical material, especially related to mean, median and mode. It is also attempted to find out alternative solutions to overcome the difficulties faced by students. The subjects in this study are 30 students at ninth grade of State Junior High School (SMPN) 1 Maluk who are selected purposively. The type of research is descriptive qualitative. Data are obtained from interviews results with two categories of difficulties, namely related to the understanding of concepts and the application of mean, median, and mode formulas. The difficulties faced by students are: (1) understanding the concepts of mean, median, and mode; (2) applying the formulas and solving problems related to mean, median and mode. The solution offered from this research is analyzing students’ difficulties in understanding mean, the number of data, and the amount of data. In deciding median, students do not pay attention to the provided data, whether it is sequential from the smallest to the largest. Meanwhile, in determining mode, students must understand that there will be three possibilities, namely, data may not have a mode, data only have one mode (single), and data have more than one mode.Keywords: Problematic, Statistics, Mean, Median, Mode.